2018
DOI: 10.1186/s12916-018-1107-6
|View full text |Cite
|
Sign up to set email alerts
|

How are health-related behaviours influenced by a diagnosis of pre-diabetes? A meta-narrative review

Abstract: BackgroundSeveral countries, including England, have recently introduced lifestyle-focused diabetes prevention programmes. These aim to reduce the risk of individuals with pre-diabetes developing type 2 diabetes. We sought to summarise research on how socio-cultural influences and risk perception affect people’s behaviour (such as engagement in lifestyle interventions) after being told that they have pre-diabetes.MethodsUsing the RAMESES standards for meta-narrative systematic reviews, we identified studies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…It is known that only approximately one-third of people identified as being at high risk of diabetes take up an offer of a lifestyle intervention programme, but there has been little exploration of reasons for this. 7,24 The findings in this current study highlight the complexity of the interplay between intrinsic personal factors and external social and environmental factors when making decisions about attendance at the NHS DPP. A recent study in New Zealand explored barriers and facilitators to dietary change in people with pre-diabetes who had been through a 6-month goal setting and dietary education programme.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
See 1 more Smart Citation
“…It is known that only approximately one-third of people identified as being at high risk of diabetes take up an offer of a lifestyle intervention programme, but there has been little exploration of reasons for this. 7,24 The findings in this current study highlight the complexity of the interplay between intrinsic personal factors and external social and environmental factors when making decisions about attendance at the NHS DPP. A recent study in New Zealand explored barriers and facilitators to dietary change in people with pre-diabetes who had been through a 6-month goal setting and dietary education programme.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
“…A recent meta-narrative review by Barry et al 7 cautions that the biomedical paradigm (which views pre-diabetes as a reversible state of abnormal glucose metabolism that can be corrected by altering an individual patient's lifestyle) leads to policy that neglects to consider the complex sociocultural environment in which people live.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of this concept concluded that there is a disconnect between actual and perceived diabetes risk and inconsistency of the measures used to calculate perceived diabetes risk among the studies 5 . A previous meta‐narrative of prediabetes supports the disconnect between actual and perceived diabetes risk in a population of persons with prediabetes 12 . It is important to increase risk perception and knowledge to promote lifestyle changes that may prevent diabetes 12 .…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, social capital can be protective for diabetes and obesity, but this is still poorly understood, particularly in the context of different education levels, socioeconomic classes, and cultures (301). For instance, in those with social capital that supports behavioral change, a diagnosis of prediabetes can lead to positive lifestyle change, but in those with inhibitions and decreased social capital, such as poor housing, low material wealth, unsupportive environments, and conflicting cultural influences, behaviors are unlikely to improve (302). Taylor et al (303) concluded that cultural competency training and experiential learning were the best ways to identify and address health disparities.…”
Section: Sociological Factorsmentioning
confidence: 99%